Knocking out FLO8 gene of Candida glabrata and its effect on EPA family - ZHAO Juntao, YUAN Jie, LIU Jinyan, CHEN Kezhi, XIANG Mingjie (Zhenduanxue lilun yu shijian)
Objective To construct a FLO8 gene knockout strain of Candida glabrata and analyze the effect of FLO8 knockout on the expression of EPA family in Candida glabrata. Methods By fusion PCR technology, the knockout components were constructed with the genomic DNA of Candida glabrata ATCC2001 strain and the plasmid DNA with screening marker NAT as templates. The knockout components were transfected into Candida glabrataATCC2001 by lithium acetate transfection method to obtainflo8△strain. The expression of EPA1, EPA6 and EPA7 genes were detected by real-time quantitative PCR. Results The FLO8 gene knockout strain of Candida glabrata was efficiently constructed. The expression levels of EPA1, EPA6 and EPA7genes in flo8△strain were significantly lower than those in ATCC2001 strain (all P<0.001). Conclusions The gene knockout method permits rapid, easy and highly efficient generation of homozygous knockout mutations in Candida glabrata. The knockout of FLO8 gene reduced the expression of EPA family in Candida glabrata, which laid a foundation for further study on its virulence mechanism.